2018
DOI: 10.3390/risks6040140
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Seasonal Affective Disorder on Selected CEE and SEE Stock Markets

Abstract: Effects of seasonal affective disorder (SAD) are explored on several selected Central and South East European markets in this study for the period 2010–2018. Both return and risk sensitivities on the SAD effect are examined for 11 markets in total (Bosnia and Herzegovina, Bulgaria, Croatia, Czech Republic, Hungary, Poland, Serbia, Slovakia, Slovenia, Romania and Ukraine). SAD effects are based upon psychiatric and behavioural theories, and are rarely observed on the stock markets today. Thus, this research pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…According to Kamstra et al [ 2 ], this trend is more salient in areas at a high latitude, where there are large differences between the length of daylight during summer and winter. Inspired by the research conducted by Kamstra et al [ 2 ], seasonal variations consistent with SAD have been reported in the pricing of initial public offerings [ 3 , 5 , 6 ], art auction prices [ 7 ], real estate prices [ 4 ], bond prices [ 8 ], as well as stock prices in several countries [ 9 , 10 , 13 ]. However, other studies have remained dubious regarding the effect of SAD on stock prices [ 24 27 ].…”
Section: Introductionmentioning
confidence: 94%
“…According to Kamstra et al [ 2 ], this trend is more salient in areas at a high latitude, where there are large differences between the length of daylight during summer and winter. Inspired by the research conducted by Kamstra et al [ 2 ], seasonal variations consistent with SAD have been reported in the pricing of initial public offerings [ 3 , 5 , 6 ], art auction prices [ 7 ], real estate prices [ 4 ], bond prices [ 8 ], as well as stock prices in several countries [ 9 , 10 , 13 ]. However, other studies have remained dubious regarding the effect of SAD on stock prices [ 24 27 ].…”
Section: Introductionmentioning
confidence: 94%
“…Kako na tim tržištima i dalje dominiraju neki čimbenici specifični za pojedine zemlje, njihovim uključivanjem u portfelj može se postići veća diversifikacija (Karkowska & Urjasz, 2022;Özer, Kamenković & Grubišić, 2020;Šego & Škrinjarić, 2018;Cevik, Korkmaz & Cevik, 2017). Također, prethodna istraživanja (Škrinjarić, 2018;Ferreira, 2018) pokazala su predvidljivost promjena vrijednosti indeksa na ovim tržištima, dugoročnu zavisnost prinosa na indekse, što podržava odbacivanje slabog oblika efikasnosti. Ovaj rad ispituje predvidljivost promjena vrijednosti na promatranim tržištima na alternativan način u odnosu na dosad korištene metode u literaturi za ova tržišta.…”
Section: Uvodunclassified
“…However, behavioral finance implies that investors' optimism and pessimism levels may have a major impact on the financial markets, supporting the likelihood that SAD will have a large impact. In light of these arguments, many studies examined the effect of SAD on various stock market returns (i.e., Gerlach, 2010;Raut and Kumar, 2020;Ruan et al, 2018;Skrinjarić, 2018;Skrinjarić et al, 2021). However, to the author's knowledge, the SAD effect has previously been studied for the Turkish stock exchange only in a multi-country context, and the findings are not particularly clear.…”
Section: Introductionmentioning
confidence: 99%